Materialidades e actantes humanos e não humanos na apropriação tecnológica em laboratórios universitários de produção audiovisual - Vargas, Emanuelly Menezes (2020)
The number of women participating in audiovisual productions has been increasing over the past two decades. It is much lower compared to the participation of men still. The lack of appropriation of this space of production is passed over by numerous actors. Following the activities of an audiovisual production laboratory at a university, this work seek to answer how the relationships and experiences of different subjects in the audiovisual production process intertwine. The objective is to understand who are the actors involved in the complex web that constitutes the experiences lived in the space of audiovisual production and how they are related to the process of appropriating or not the technologies of audiovisual production and to develop audiovisual producers. A methodological pathway is built based on ethnography, referring Mariza Peirano (2014), Claudia Fonseca (1999) and Urpi Uriarte (2012), and on cartography, referring Nísia Martins do Rosário (2016) and Deleuze and Guattari (1995). Bruno Latour (2012), Tim Ingold (2012, 2015) and Donna Haraway (1995, 2009) are references on the construction of a reflection heterogeneous associations in audio-visual production laboratories and the appropriation process. The reflection on gender is through Joan Scott (1989) and Avtar Brah (2006). To think about how technology is built, authors like Judy Wajcman (2006) and Donna Haraway (2009) are referenced. The discussion about appropriation was based on authors like Serge Proulx (2016a, 2016b) and María Isabel Neüman (2008). At last, it’s presented and discussed six groups of heterogeneous associations that help to comprehend the actants involved in such process, under a reflexive and intersectional perspective of gender, race and class. Addresses relations link: technology and the question of domestic space, the relation between students and professors, the relation between internship and learning, access to employability and equipment, affinities between colleagues, race and the experience of being a woman, and the multiplicity of associations between people and laboratory equipment.